Measuring Complexity in the Artistic Representation of the Architecture of Balkrishna Doshi - Lionar, Mario Lodeweik (Journal of Architectural Research and Design Studies, 2022)
Besides his architectural works, Indian architect Balkrishna Vithaldas Doshi is also renowned for expressing his ideas through his paintings. Inspired by Indian-Mughal miniatures, these paintings present his architectural works by depicting an idea so prevalent in Indian culture as well as in his works: complexity. To investigate this notion in a quantitatively measurable manner, this paper investigates one of the architect’s most significant works, Sangath, depicted both in Doshi’s painting and in the form of conventional orthographic drawings, using a comparative fractal dimension analysis. The result proves that the fractal dimension of Doshi’s painting of Sangath is significantly higher than those of the orthographic drawings showing the building’s exterior: block plan, front elevation, and right elevation. The conclusion suggests that Doshi’s painting is capable of presenting an idea of complexity more prominently than conventional architectural drawings. Keywords: Balkrishna Doshi; fractal analysis; fractal dimension; Indian-Mughal miniature paintings; visual complexity